STUDENTS’ DISTANCE LEARNING COPING STRATEGIES: AN ANALYSIS FROM THE PERSPECTIVE OF SDG NUMBER 4 - Oktaviani, Maya; Hasanah, Uswatun; Faesal, Muhammad; Elmanora, Elmanora; Zulfa, Vania (UI Scholars Hub, 2022)
During the COVID-19 pandemic, the government had implemented a policy which changed face-to-face learning to distance learning. However, there is still a need for teachers to optimize the quality of students' education. This goal is in line with Sustainable Development Goals (SDGs) number four, namely quality education. By getting a quality education, people can break the chain of poverty. Through education, inequality can be reduced, and people can be empowered to live more sustainably and healthily. The purpose of this research was to analyse students' coping strategies during distance learning. This research uses a quantitative approach with a survey method. The research was conducted in Jakarta from May to June 2021. The population was Universitas Negeri Jakarta students. The sample was selected using a cluster sampling technique of as many as 211 students. Data collection uses a coping strategy scale consisting of 39 items derived from the dimensions of problem-focused coping, emotional-focused coping, and seeking social support. The t-value of 0.110 with sig 0.913 > 0.05 shows no significant difference in average coping strategies between female and male respondents. The ANOVA revealed F-value of 0.329 with sig. 0.805 > 0.05, which means there is no significant difference in the average coping strategy of respondents based on birth order. The results of the analysis showed that the students' coping strategies were in the high category. Over time, students can adapt to the learning techniques used in the classroom. The problem-focused coping dimension has the highest average value, so this research concludes that students focus on dealing with the problem when faced with one. Students try to analyse the causes of the problems they face, plan steps to deal with problems, and make efforts to change the situation carefully. There is no difference in the average value of female and male students' coping strategies. Students are more dominant in using problem-focused coping as an effort to deal with stress when implementing distance learning. Students must be able to overcome their problems with appropriate coping strategies to achieve quality learning in education.